A method for accurate determination of terminal sequences of viral genomic RNA. - Weng, Z; Xiong, Z (Genome Research, 1995)
A combination of ligation-anchored PCR and anchored cDNA cloning techniques were used to clone the termini of the saguaro cactus virus (SCV) RNA genome. The terminal sequences of the viral genome were subsequently determined from the clones. The 5' terminus was cloned by ligation-anchored PCR, whereas the 3' terminus was obtained by a technique we term anchored cDNA cloning. In anchored cDNA cloning, an anchor oligonucleotide was prepared by phosphorylation at the 5' end, followed by addition of a dideoxynucleotide at the 3' end to block the free hydroxyl group. The 5' end of the anchor was subsequently ligated to the 3' end of SCV RNA. The anchor-ligated, chimerical viral RNA was then reverse-transcribed into cDNA using a primer complementary to the anchor. The cDNA containing the complete 3'-terminal sequence was converted into ds-cDNA, cloned, and sequenced. Two restriction sites, one within the viral sequence and one within the primer sequence, were used to facilitate cloning. The combination of these techniques proved to be an easy and accurate way to determine the terminal sequences of SCV RNA genome and should be applicable to any other RNA molecules with unknown terminal sequences.